ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI SENAM IRAMA TERHADAP PENURUNAN INDEKS MASSA TUBUH PADA ANAK USIA SEKOLAH DI RT 01 RW 04 KELURAHAN SUKAMAJUBARU KECAMATAN TAPOS KOTA DEPOK - Defina Ramandhani (2022)
Obesity is a global health problem with an increasing incidence in both developed and developing countries. Obesity in school-age children affects health problems and increases the risk of disability in adulthood. Low physical activity has an impact on declining health and fitness so it can increase the risk of obesity. Rhythmic gymnastics is one form of overweight and obesity management that can reduce body weight and body mass index. This study aims to analyze nursing care with rhythmic gymnastics interventions to decrease body mass index in school-age children. The intervention was carried out 3 times a week for managed patients and resumed patients at RT 01/RW 04 Sukamajubaru, Tapos Depok. The results of the implementation for 4 weeks showed that there was a weight loss in managed patients by 1.7 kg with a decrease in BMI of 0.60 SD and in resume patients by 2 kg with a decrease in BMI of 0.59 so it can be concluded that the rhythmic gymnastics intervention has an effect on the decrease in body mass index in school-age children. Community nurses are expected to be able to apply rhythmic gymnastics as one of the management in overcoming overweight and obesity in school-age children. Keywords: School Age Children, Obesity, Rhythm Gymnastics